2007
DOI: 10.1051/apido:2007024
|View full text |Cite
|
Sign up to set email alerts
|

Composition of volatiles from fermenting pollen dough and attractiveness to the small hive beetleAethina tumida, a parasite of the honeybeeApismellifera

Abstract: -The response of the small hive beetle (SHB), Aethina tumida Murray, to volatiles from a pollenbased diet conditioned by the feeding of 100 adult virgin female or male SHBs (4-8 weeks old) for 1, 3, 7 or 14 days is described and compared to that of the same diet inoculated with the yeast Kodamaea ohmeri (NRRL Y-30722), isolated from the beetle. In a wind tunnel, volatiles from pollen dough conditioned by beetles of either sex for 3 or 7 days lured significantly more beetles into traps than volatiles from uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…This study is the first to report the development of SHB‐attracting volatiles from honeycomb and brood comb from honeybee hives that have been infected with SHB. It builds on previous studies which investigated the volatiles emanating from SHB‐conditioned pollen dough, a mixture of harvested pollen and honey (Arbogast et al., , ; Torto et al., ). In using natural hive materials we were able to produce a similar mix of SHB‐attracting volatiles for which the attractiveness persisted for much longer than in previous reports (Torto et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first to report the development of SHB‐attracting volatiles from honeycomb and brood comb from honeybee hives that have been infected with SHB. It builds on previous studies which investigated the volatiles emanating from SHB‐conditioned pollen dough, a mixture of harvested pollen and honey (Arbogast et al., , ; Torto et al., ). In using natural hive materials we were able to produce a similar mix of SHB‐attracting volatiles for which the attractiveness persisted for much longer than in previous reports (Torto et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Work in the USA has shown that SHB are attracted to a range of hive odours, particularly the odour of adult worker bees and fermenting pollen dough, a hive product substitute (Suazo et al, 2003;Torto et al, 2005Torto et al, , 2007aNolan & Hood, 2008). The aim of this study was to investigate the changes in volatile profiles of honeycomb and brood comb from different sources that have been altered by the action of developing SHB larvae and yeast, and explore changes in attractiveness of these hive products to SHB.…”
Section: Introductionmentioning
confidence: 99%
“…There were two traps at each site, suspended Ϸ1 m above the ground on supports made with two sections of steel pipe connected at right angles to form a pole with a horizontal arm. The bait consisted of pollen dough inoculated with the yeast K. ohmeri (Torto et al 2007a). Insecticidal strips (Vaportape II; Hercon Environ- mental, Emigsville, PA) were used to kill adult beetles and prevent the occurrence of large numbers of larvae in the bait.…”
Section: Methodsmentioning
confidence: 99%
“…Bottom board traps, as previously described (Torto et al 2007b), were baited with inoculated pollen dough (50 g), which was prepared by mixing K. ohmeri with double-distilled water and commercial pollen dough (4% pollen with sugar, soy, yeast, and water; Global Patties, Airdrie, Alberta, Canada) at 1:100:1,000 by wt, and allowing the dough to ferment for 5 d (Torto et al 2007a).…”
Section: Methodsmentioning
confidence: 99%